Evaluation and engagement in journalistic commentary and news reportage - Marín Arrese, Juana Isabel; Núñez Perucha, Begoña (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2006)
This paper explores the expression of evaluation and the treatment of 'the same event' in news reportage and journalistic commentary in two languages (English, Spanish). In our analysis of the evaluative dimension, we draw on the framework of Appraisal Theory (Martin 2000; Martin and White 2005; White 2003, White 2004, inter alia), and elaborate on the analysis of the categories of evaluation, subsumed under the notion of Engagement, in relation to writer stance and to the dimension of subjectivity and intersubjectivity. The paper reveals the presence and patterning of the various linguistic resources for the expression of evaluation in these subgenres of journalistic discourse, and establishes comparisons across languages.